PERLUNYA ATS ROUTE ANTARA PKN VOR DAN POIN SUMDI UNTUK OPTIMALISASI LALU LINTAS PENERBANGAN DI PANGKALAN BUN CONTROL ZONE (CTR) DAN TERMINAL CONTROL AREA (TMA) - Afrizal Wahiddin Samsudin Tengku Idris; Dani Chandra Yudo Pranoto; Abdul Mu’ti Sazali (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
ATS route is a special route designed to facilitate the flow of air traffic as required in the provision of air traffic control services. However, at Pangkalan Bun there are still flight paths that use direct instructions, one of which is the scheduled flight path to Ahmad Yani Airport Semarang which uses the SUMDI direct point instruction, even though the number of scheduled flights to and from Ahmad Yani Airport Semarang via SUMDI points is the most congested air route with 10 scheduled flights per day out of a total of 30 scheduled flights at Iskandar Airport.This study aims to provide input regarding the need for the Pangkalan Bun ATS route to Semarang and Surabaya in order to optimize the provision of air traffic services in the Pangkalan Bun Control Zone (CTR) and Terminal Control Area (TMA). The research method used in this research is descriptive qualitative using data collection techniques in the form of interviews, observations and literature studies. The source of data and research was obtained from Perum AirNav Indonesia LPPNPI KCP Pangkalan Bun, and addressed to ATC personnel stored at Perum AirNav LPPNPI KCP Pangkalan Bun. The results showed that the ATS route between Pangkalan Bun, Surabaya and Semarang often conflicted, so the ATS route was needed to facilitate flight traffic guides in providing services so that flight traffic services at CTR and TMA Pangkalan Bun could be more optimal.